Maintenance of service delivery during medical countermeasures deployment: The association between the COVID-19 vaccine rollout and continuity of routine childhood immunization services in Uganda. - Steven Ndugwa Kabwama; Neda Razaz; John M Ssenkusu; Helena Lindgren; Rhoda K Wanyenze; Alfred Driwale; Tobias Alfvén (PLOS Global Public Health)
COVID-19 vaccines significantly reduced COVID-19 related morbidity and mortality. Although purposeful response measures like movement restrictions affected delivery of other health services, few studies have investigated the association between COVID-19 vaccination as a response strategy and continuity of other immunization services. We aimed to assess the association between the COVID-19 vaccine rollout and continuity of routine immunization services and describe the interventions instituted to maintain delivery in Uganda. This was a cross-sectional study conducted in Wakiso District, Central Uganda. We applied an explanatory, sequential mixed-methods design. We analyzed routine childhood immunization data by computing the percentage change in vaccine doses given for Bacille Calmette-Guerin (BCG), Diptheria, Tetanus Toxoid Pertussis (DPT3), Polio 0, Polio 1, Polio 2 and Polio 3 between March 2021 and April 2021. This was followed by 19 interviews with health workers and 3 focus group discussions with altogether 33 mothers using the World Health Organization Health System Building Blocks as a guiding framework. We found that the COVID-19 vaccine rollout was associated with changes in the trends of routine vaccine uptake. The number of DPT3 vaccine doses reduced by 4.3% between March 2021 and April 2021 after the COVID-19 vaccine rollout while that for Polio 1 vaccine doses reduced by 5.5%, Polio 2 vaccine doses reduced by 5.8% and Polio 3 doses reduced by 5.6%. The challenges to continuity included increased workload, competition for cold chain and storage capacity and impact on perceptions about vaccination. Interventions to sustain demand included engaging community health workers, community mobilization, health education, and prioritizing routine immunization services. Interventions to maintain delivery included integration of services, increasing health workforce and separating resources for routine vs COVID-19 vaccination. In conclusion, the COVID-19 vaccine rollout was associated with infrastructural and logistical challenges which affected delivery of routine immunization services. Introduction of the COVID-19 vaccines was also associated with negative perceptions about routine childhood vaccines. Deployment of new medical countermeasures should integrate interventions to predict and mitigate effects on existing supply systems like the human resources and infrastructure. Medical countermeasures deployment should also involve education and sensitization that addresses misconceptions and sustains demand for existing health services.